Rare Entities of Mixed Phenotypic Acute Leukemia: Are They Really So Rare? Largest Series of B+T MPAL - H .V., Raghavendra; N R, Namrata; C. Raghu, Vijay; K Chinnagiriyappa, Lakshmiah (International Journal of Medical Research and Review, 2016)
Background: MPAL are rare, accounts 4% of acute leukemias. B+T MPAL are extremely rare. There is no robust information on the clinical and biologic features of these leukemias. Present study from kidwai memorial institute of oncology focused on MPAL rare types, especially B+T MPAL. Design and Methods: We attempted to classify MPAL, based on WHO 2008 classification and attempted to summarise diagnostic criteria, cytochemistry, immunophenotyping, cytogenetics & clinical features of B+T MPAL. Results: Most MPAL cases reported were B/Myeloid, followed by B+T MPAL, T+Myeloid , undifferentiated and unclassifiable leukemias respectively. Conclusion: Among MPAL unusual high incidence of B+T MPAL (38.4%) was noted. Overall median survival was 5 years.